Chimica, Materiali e Sostenibilità - Cecchi, Teresa (Chimica nella Scuola, 2024)
Sustainability is one of the most used words in communication and perhaps it is sometimes abused. It is certainly unachievable without the chemical skills necessary for the transition from the linear economy (plunder, consume, throw away) to the circular one (recovery, transform, reuse), that is the cornerstone of the ecological transition. The laboratory teaching practice is renewed by taking inspiration from the 17 objectives of the 2030 Agenda. Making students aware of the key role of chemistry in harmoniously attending to the planet, profit and people is fully a civic education action.